Procedure of Possession and Contributions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The topic of possessive suffixes in nouns is difficult for elementary school students, because until this topic is studied, students have not yet been introduced to the concept of "person" and have not yet learned personal pronouns.